Rethinking performance measurement : beyond the balanced scorecard - Meyer, Marshall W. (Cambridge University Press, 2002)
A major new study by a leading management scholar from top-ranked Wharton School of Business on problems of performance measurement systems. Highlights particular shortcomings of the widely adopted 'balanced scorecard' technique. Outlines an alternative approach capturing fundamentals of firm performance. Essential reading for management faculty, MBA students and thoughtful practitioners.